LAYANAN E- PENGADUAN SATUAN TUGAS PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL BERBASIS WEB - Dahoklory, Melda; Alyona, Caryl; Dien, Marion Erwin; Agustina, Elsa Nania; Lalaun, Albertus (JURNAL SIMETRIK, 2025)
Sexual violence is a crime that threatens the integrity and dignity of individuals, and disrupts public order and security. Based on survey data from the Directorate General of Higher Education, Research, and Technology in 2020, 77% of lecturer respondents stated that cases of sexual violence occurred in universities, but 63% of respondents from the victim side chose not to report their cases to the authorities. In addition, universities are the third location for sexual violence with a percentage of 15%. In response to this, the Ambon State Polytechnic (POLNAM) has formed a task force for the prevention and handling of sexual violence (SATGAS PPKS) as an effort to prevent and handle acts of sexual violence that occur in the POLNAM environment. The PPKS Task Force is tasked with providing assistance, guidance and information related to the prevention and handling of sexual violence within the scope of the POLNAM campus. Based on data and information from the Polnam PPKS Task Force Team, there has never been any reporting of sexual violence committed by students. This is due to the lack of information on the existence of the Polnam PPKS Task Force and also the flow of the reporting process and filling out the complaint data form. This process is carried out manually by visiting the Polnam PPKS Task Force and filling out the complaint form. Although efforts have been made to prevent and handle sexual violence, there are obstacles that affect the effectiveness and efficiency of the reporting and handling process. One of the factors that causes minimal reporting is the fear of the confidentiality of victims and reporters when visiting the PPKS Team. So based on this background, a media is needed that acts as a container for Polnam PPKS information which also handles the Internal PPKS reporting process. Electronic complaints are electronic-based systems or platforms that allow the public to submit complaints, suggestions, or aspirations related to public services or the performance of government agencies online. The development of this system uses the Prototype Process Model Software development method. This study aims to implement a prototype of a sexual violence e-complaint system. This system acts as an electronic information media related to PPKS Polnam and the reporting complaint service process related to the work area of SATGAS PPKS at Ambon State Polytechnic. Keywords: e-Complaints, Task Force, Polnam, PPKS, Violence,